Continuity and Focus in Criminal Justice Research - Zimring, Franklin E. (Journal of research in crime and delinquency, 1993)
In recent times, criminal justice has become more a topic than disciplines a topic studied by persons from a variety of different perspectives using different languages and different empirical tools. All they share is a subject matter. No doubt this diversity encourages fresh approaches and pluralism in research, but it does so at a price. The tower of Babel, it will be remembered, also could have been called an interdisciplinary enterprise. Authors' remarks are put forward in two installments. First, they provide some critical scrutiny of the two explicitly theoretical essays, those by social scientists Lawrence W. Sherman and John Braithwaite. Second, authors consider the case for a criminological focus on violent behavior, an emphasis that should be added before one uses the main essays here as a road map of the future of criminological research. Although there has been little movement toward a major emphasis on violence in recent criminology, much medical and public health research in the 1990's has concentrated on lethal violence. To some extent, the new wave of medical concern has compensated for the lack of criminological attention. But the social and cultural sophistication of the criminologist is much needed in the next chapter of research on violence. The problem deserves all the criminological energy and attention that progress in the understanding of violence control will require